Under the Sign of Catastrophe: Actuality and Historicity from the Critical Theory (Palimpsesto, 2019)
The notes composing this paper, assembled in an essayistic and fragmented manner, aim to guide a reading plan that confront the contemporary, or neoliberal, experience of time, and the regime of historicity implied in it, to Benjamin's notion of "catastrophe". It attempts to revisit the "critical power" of the dialectic, as worked out by the Critical Theory of Society, especially in Adorno (1982; 1991; 2013; 2015) and Benjamin (1994; 2007; 2011; 2013) and present in contemporary thinkers such as Agamben (2004; 2014) and Žižek (2011; 2014; 2016) to argue for a non-totalized interpretation of reality. The objective is argue the link, although not evident, of politics in relation to the historicity of subjectivity and to epistemological theories, specifically to the theory of History.
Keywords: Critical Theory of Society; Historical Time; Catastrophe; Neoliberalism